Health Service Utilization by Elderly Population in Urban Nepal: A Cross-Sectional Study - Gurung, L.B.; Paudel, G.; Yadav, U.N. (Journal of Manmohan Memorial Institute of Health Sciences, 2016)
Background The elderly population is in increasing trend all over the world. Elderly people experience many physiological, biological and psychological changes. The general objective of the study is to assess the utilization of health care services among the elderly population of Butwal sub-metropolitan city. Methods A quantitative descriptive-cross sectional study, with a total number of 212 elderly people residing in Butwal sub-metropolitan city, was selected for the study purpose. The study period was from March to October 2015. The samples were randomly selected from the sampling frame of 3 different wards of Butwal sub-metropolitan city. Information was collected using an interviewer administered semi-structured questionnaire. Chi-square test was used to identify the factors associated with the utilization of health care services among elderly population. Results Our findings reveal that 84.4% of elderly people visited to the health facility during past 1 year. There were more females (50.9%) than males (49.1%). Majority of elderly people were diagnosed with one of the chronic ailment; were under regular medication. More than 4/5th (84.9%) of older adults rated “satisfactory” to their health condition. Monthly family income, chronic disease, elderly on medication and self-rated health status are statistically significant with utilization of health care services at 95% level of confidence. Conclusions The finding suggests that monthly family income, chronic disease, elderly on medication and self rated health are strongly associated with utilization of health care services by elderly people. Thus the study suggests further interventions to improve the health care service utilization by elderly people. Journal of Manmohan Memorial Institute of Health Sciences Vol. 2 2016 p.27-36